Site selection of desert solar farms based on heterogeneous sand flux - Guoshuai Li; Lihai Tan; Bao Yang; Tao Che; Guangcai Feng; Fredrik Charpentier Ljungqvist; Yayong Luo; Heqiang Du; Hui Zhao; Ying Zhang; Chunlin Huang; Ning Huang; et al. (npj Climate and Atmospheric Science, 2024)
Abstract Site selection for building solar farms in deserts is crucial and must consider the dune threats associated with sand flux, such as sand burial and dust contamination. Understanding changes in sand flux can optimize the site selection of desert solar farms. Here we use the ERA5-Land hourly wind data with 0.1° × 0.1° resolution to calculate the yearly sand flux from 1950 to 2022. The mean of sand flux is used to score the suitability of global deserts for building solar farms. We find that the majority of global deserts have low flux potential (≤ 40 m3 m-1 yr-1) and resultant flux potential (≤ 2.0 m3 m-1 yr-1) for the period 1950–2022. The scoring result demonstrates that global deserts have obvious patchy distribution of site suitability for building solar farms. Our study contributes to optimizing the site selection of desert solar farms, which aligns with the United Nations sustainability development goals for achieving affordable and clean energy target by 2030.